Retracted: Company Income Tax: A Sine Qua Non to Economic Growth of Nigeria - Egbere Michael Ikechukwu (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Although company income tax (CIT) remains a critical instrument for financing public services and infrastructure, its contribution to economic growth in Nigeria is constrained by persistent revenue leakages associated with capital flight. This study examines the extent to which capital flight undermines the effectiveness of CIT in supporting Nigeria’s economic growth. Drawing on an adapted model from Ichoku and Fonta (2006) and anchored in Wagner’s Law of expanding state activity, the study employs time-series data from 1994 to 2016 and applies the Error Correction Model (ECM), Augmented Dickey-Fuller unit root tests, Johansen cointegration tests, and Granger causality tests to evaluate both short-run and long-run relationships between capital flight components and CIT revenue. The findings show that over-invoicing and under-invoicing exert a statistically significant negative effect on CIT, indicating that these illicit financial practices erode the corporate tax base and weaken government revenue generation. The results also reveal both unidirectional and bidirectional causal relationships between capital flight indicators and CIT. Although debt servicing exerts a negative but statistically insignificant effect, its long-term implications for fiscal sustainability remain substantial. The study concludes that CIT is indispensable to Nigeria’s economic growth, but its effectiveness is severely compromised by unchecked capital flight. These findings underscore the need for stronger customs enforcement, improved tax administration, and enhanced international cooperation to curb illicit financial flows, strengthen tax compliance, and reinforce Nigeria’s fiscal capacity.